Antibacterial activity and phytochemical analysis of Garcinia mangostana L. leaf extracts against Xanthomonas oryzae pv. oryzae and Pseudomonas syringae pv. tomato - Mohammed Naji, Qamar (2016)
The immense diversity of plant pathogens, which include viruses, bacteria, fungi, nematodes, and insects, approximates 7100 species. Among these, roughly 150 are bacterial species that cause diseases to plants. Bacterial plant diseases are most frequent and severe in tropical and subtropical places, where warm and humid conditions like Malaysia are ideal for bacterial growth. Indeed, consistent annual crop losses are recorded in all countries. The problem of plant diseases is depended on chemical control as antibiotic. This chemical control is very expensive and yet not very effective against for many bacterial diseases. In this study, the leaf of mangosteen was used to prepare extract to bio-control for two types of plant pathogens namely Pseudomonas syringe pv. tomato and Xanthomonas oryzae pv. Oryzae. The potential of mangosteen (Garcinia mangostana L.) leaf extract as a biological control agent against plant pathogenic bacteria which are responsible to decrease the quality and volume of crop production worldwide was assessed. Extract was obtained by maceration of the leaves using chloroform, n-hexane, and methanol. Crude extracts of about 1.45 % were derived using chloroform, 1.25 % using n-hexane, and 1.65 % using methanol leaf crude. Compared to chloroform and n-hexane, effective extraction of readily soluble compounds was observed in case of methanol, as the highest yield was collected from it. For the in-vitro antibacterial activity, two plant pathogenic bacteria, namely Pseudomonas syringe pv. tomato and Xanthomonas oryzae pv. oryzae were acquired. Four different concentrations of 12.5, 25, 50, and 100 mg/mL were used through the cup-plate agar diffusion technique. Streptomycin sulphate at 30 μg/mL concentration was set as a positive control, whereas every respective solvent used in the leaf extraction was set as negative controls. The highest diameter value of inhibition zone was observed in P. syrange pv. tomato at all range of concentrations, followed by X. oryzae pv. oryzae. Since only the methanol extract demonstrated antibacterial activity, it was the only solvent subjected in the assay for minimum bactericidal concentration (MBC) and minimum inhibitory concentration (MIC) determination. The least methanol extract concentration utilised in MIC assay was at 1.56 mg/mL, inhibiting X. oryzae pv. oryzae followed by P. syrange pv. tomato at a concentration of 3.13 mg/mL. This assay indicated that methanol extract caused bactericidal impacts at concentrations of 1.56 mg/ml and 3.13 mg/ml for varying plant pathogenic bacteria species. The least concentration of MBC noted was at 3.13 mg/mL against X. oryzae pv. oryzae and 6.25 mg/mL against P. syrange pv. tomato. Mangosteen methanol leaf extracts’ primary phytochemical screening indicated the existence of flavonoids, alkaloids, saponins, tannins, anthraquinones, terpenoids, and phenols. When visualised in the thin layer chromatography (TLC) profiling of methanol extract using acetone and n-hexane in a ratio of 6:4 (v/v) gave 11 maximum colourful bands. Retention factor (Rf) values proved the presence of various active secondary metabolites within the methanol extract. Methanol extract’s antibacterial activity was screened through the direct bioautography procedure. The intention was to determine the location of active bands on chromatograms developed for TLC profiling in the same manner. The most active Rf values that inhibited every tested plant pathogenic bacteria at the same location of Rf values were noted at 0.93, 0.86, 0.66, 0.46, 0.33 and 0.16. A comparison of the Rf values acquired was made with earlier studies utilising the same solvent system. Antibacterial impacts of the most effectual extract of mangosteen crude were supported by the existence of chemical components identified by Gas Chromatography-Mass Spectrometry (GC-MS). The G. mangostana leaf extract was exhibited good potential to be used to inhibit growth of Xanthomonas oryzae pv. oryzae and Pseudomonas syringae pv. tomato invitro. The results showed that methanol extract demonstrated antibacterial activity when tested on the plant pathogenic bacteria in-vitro. On the other hand, chloroform and n-hexane did not exhibit any antibacterial activity against plant pathogenic bacteria, as there was no inhibition zone noted under these treatments. Cycloartenol, caryophyllene, docosane, and 4, 4-methylenebis (2, 6-di-tert-butylphenol) were noted as key compounds in the mangosteen leaf extract.